Optical coherence tomography and optical coherence tomography angiography in glaucoma: diagnosis, progression, and correlation with functional tests - Triolo, Giacinto (Ther Adv Ophthalmol, 2020)
The present review will summarize the most updated findings with regards to optical coherence tomography and optical coherence tomography angiography in glaucoma, highlighting their clinical use for detection and monitoring of the disease, and their correlation to functional tests (such as visual field) widely employed in the asset of modern glaucoma clinics.